PENGARUH PEMBELAJARAN KITAB WASHOYA TERHADAP MORAL PESERTA DIDIK KELAS V MADRASAH DINIYAH AN-NUR DESA PUTER KECAMATAN KEMBANGBAHU KABUPATEN LAMONGAN TAHUN PELAJARAN 2022/2023 - Ansori, Mahfud; Ni’mah, Khoirotun; Sa’adah, Hurin Innihayatus (Fakultas Agama Islam, 2024)
Moral education is carried out in order to create awareness among educators and students as well as the learning process so that students can actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, good morals, and skills. needed in the life of society, nation and state. The purpose of this study was to answer the question: how to study the book of washoya for students V of Madrasah Diniyah An-Nur Puter Kembangbahu Lamongan in the 2022/2023 Academic Year?. How are the morals of class V students at Madrasah Diniyah An-Nur Puter Kembangbahu Lamongan for the 2022/2023 academic year? Is there any effect of learning the washoya book on the morals of fifth grade students at Madrasah Diniyah An-Nur Puter Kembangbahu Lamongan for the 2022/2023 academic year? The results of the research can be concluded into three things, namely: (1) the interest in learning the book of washoya for fifth grade students at Madrasah Diniyah An-Nur Puter Kembangbahu Lamongan for the 2022/2023 academic year is moderate. This is evidenced by the results of the questionnaire which showed the value of 40% who answered was, at intervals of 33-38. (2) The moral level students V of Madrasah Diniyah An-Nur Puter Kembangbahu Lamongan in the 2022/2023 Academic Year is classified as moderate. This is evidenced by the results of the questionnaire which showed a moderate value of 60%, namely at intervals of 36-40. (3) the relationship between learning the washoya book and the morals of fifth grade students at Madrasah Diniyah An-Nur Puter Kembangbahu Lamongan for the 2022/2023 academic year has moderate or moderate influence. This can be proven tcount (0.480) > ttable (0.444) significance and value (0.03) (0.05) < and the interpretation in the table is the value 0.40 – 0.70 so that there is a correlation between variable X and variable Y ie or pretty.